Democracy and Poverty: A Lesson from Mongolia - Tuya, N (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i18.66 Mongolian Journal of International Affairs No.18 2013: 11-15